Stereophotogrammetry and relief photography in the assessment of foot disorders. Issue 1 (February 1981) - Craxford, A D; Rutherford, A; Evans, M S; Park, C
Abstract : Expanded polyethylene foam (Plastazote) is used in the treatment of rheumatoid, diabetic, and leprotic foot disorders. This paper describes a diagnostic use for this material. Two photographic techniques combine to give vivid and quantitative representations of foot deformities which are easily applicable to clinical use. Relief photography uses illumination to create an illusion of solidity in a 2-dimensional photography. Stereophotogrammetry produces contour plots from stereopairs of photographs of the Plastazote footprint. After use the impressions are trimmed and slipped into the patient's shoes in the same way as any other foam insole.